(untitled) (Annals of Medical Research, 2021)
Aim: Atrial fibrillation is a common complication after coronary bypass surgery. There are various studies aimed at predicting the development of postoperative atrial fibrillation (POAF). Low vitamin D status has been associated with an increased risk of cardiovascular disease. Atrial fibrillation (AF) is the most common cardiac arrhythmia. We purpose to evaluate the effect of serum 25(OH) vitamin D level on the development of POAF after cardiac bypass surgery (CABG). Material and Methods: Our study is a retrospective chart review which all patients who underwent isolated, elective, on-pump CABG operation between January 2017 and January 2018. POAF was defined as the development of atrial fibrillation after the completion of cardiac surgery, which required intervention.The whole study population divided into two groups: group I, patients who developed POAF and group II, patients who did not.Ejection fraction and left atrium diameter of participants were recorded. 25(OH)D and parathormone values, as well as other demographic and clinical characteristics, were collected. Results: A total of 78 patients were available for analyses. While 61 patients did not develop POAF, 17 patients developed. The rate of POAF was 22%. The median ages of the patients with and without POAF were significantly different (61(54-72) vs. 69(65-77) years, p=0.012). The left atrial diameter was larger in patients with POAF (p=0.025). Preoperative ejection fractions were not different between the groups. Total bypass time and cross-clamp time were not significantly different. Although the mean value of preoperative 25(OH)D level was slightly higher in patients who did not develop POAF compared to that of patients with POAF, the difference was not statistically different between the groups. Conclusion: Preoperative 25(OH)D levels were not different between the patients with and without POAF.